Analisis Penggunaan Digital Marketing Dalam Meningkatkan Penjualan Smartphone Vivo Di Toko Pasar Hp Gunungsitoli - Waruwu, Asteti; Mendrofa, Yupiter; Waruwu, Meiman Hidayat; Gea, Nov Elhan (LPPM Universitas HKBP Nommensen, 2024)
This research aims to determine the use of Digital Marketing, the obstacles to Digital Marketing, and the sales level of Vivo cellphones in the Gunungsitoli City HP Market Store. This research uses a qualitative method whose data sources are taken from documentation, interview results and observation results. In this research, interviews were conducted with various questions about the research topic directly. The results of this research show that the Gunungsitoli City HP Market Shop using Digital Marketing makes it easier to introduce goods for sale and offer to the public as well as knowing the obstacles in using Digital Marketing to increase sales at the Gunungsitoli City Toko Pasar HP.